The sedimentology and chemostratigraphy of the Nafun Group, Huqf Supergroup, Oman - McCarron, M; McCarron, M. E. Gretta (1999)
﻿ Two glacial units have been identified within the Abu Mahara Group, with the upper being overlain by a 'cap carbonate' (the Hadash Formation). Ash beds from the lower glacial unit are dated herein by U-Pb zircon methods at 723+107-16 Ma. The Hadash Formation is succeeded by the Naftm Group which is overlain by the volcaniclastic Fara Formation. An ignimbrite unit within the Fara Formation is dated herein by U-Pb zircon methods at 544±3.3 Ma. The lithologies of the Nafun Group are found to indicate shallow marine deposits in the Huqf area of east-central, Oman and more distal deposits in the Oman Mountains of north Oman. The east-central Khufai Formation carbonates shoal-upward from mid-ramp settings to intertidal carbonates with outer-ramp carbonates in the Oman Mountains. There was arguably a slight draw-down in the uppermost Khufai Formation before the drowning of the carbonate ramp by the Shuram Formation siliciclastics. These red and green siliciclastics are typically swaley cross-stratified upward, indicative of storm deposition. An increase in carbonates in the upper Shuram Formation leads gradationally into the lower Buah Formation. The Buah Formation carbonates preserve another upward-shoaling trend from subwave base to sabkha deposits in east-central Oman. In Wadi Bani Awf, the coeval sediments are shown to contain slump structures and brecciated beds of the ramp slope, with thick breccia units representing slope failure deposits. The Oman Mountains therefore preserves the margin of a carbonate platform. The dramatic positive and negative to positive excursions recorded in the stable isotope stratigraphy through the Nafun Group are argued to largely reflect sea water δ13C signatures and may perhaps be explained in terms of climatic changes identified lithologically. The top of both carbonate formations are sequence boundaries with the maximum flooding surfaces identified within the siliciclastic formations.